A Biallelic Variant in FRA10AC1 Is Associated With Neurodevelopmental Disorder and Growth Retardation. (7th August 2022) - Alsaleh, Norah; Alhashem, Amal; Tabarki, Brahim; Mohamed, Sarar; Alharby, Essa; Alkuraya, Fowzan S.; Almontashiri, Naif A.M.
Abstract : Objectives: Our objective was to identify the genetic cause in a family with a remarkable history of neurodevelopmental disease and growth retardation. Methods: A neurologic evaluation was performed, and DNA samples were obtained from the affected siblings and parents to perform whole-exome sequencing (WES). Results: Both siblings presented with dysmorphic features, failure to thrive, global developmental delay, generalized hypotonia, feeding problems, and congenital heart disease. WES revealed a homozygous nonsense variant in the FRA10AC1 gene in both siblings. Discussion: A recent study has reported the first association of biallelic variants in the spliceosomal C complex gene, FRA10AC1, with syndromic neurodevelopmental disease and growth retardation in 5 patients from 3 consanguineous families complex. In this study, we provide the first confirmation of the reported FRA10AC1 -related neurologic syndrome in an additional family.